Occupational exposure levels to wood dust in Italy, 1996–2006. Issue 8 (17th December 2007) - Scarselli, A; Binazzi, A; Ferrante, P; Marinaccio, A
Abstract : Background: Wood dust has been classified as carcinogenic to humans and the association with nasal cancer risk has been observed in a large number of epidemiological studies. Objectives: The aim of this study is to summarise data about occupational exposure levels to wood dust in Italy and to examine some exposure determinants. Methods: Exposure measurements on wood dust were extracted from the SIREP (Italian Information System on Occupational Exposure to Carcinogens) database between 1996–2006. Descriptive statistics were calculated for exposure-related variables using univariate analyses. The prevalence of elevated exposure levels was estimated overall and for some industrial sectors. A multifactorial analysis of variance was performed to determine which factors influenced exposure levels to wood dust. Results: The total number of exposure measurements (n) reported is 10 837, which refer to 10 528 workers and 1181 companies. The overall arithmetic mean is 1.44 mg/m 3 and the geometric mean is 0.97 mg/m 3 . Industrial sectors at high risk are "manufacture of wood and wood products" (n = 5539) as well as "manufacture of furniture" (n = 4347). About 74% of exposure measurements report a value <2 mg/m 3 . In the multifactorial analysis, it has been found that job category, industrial sector, company size and geographical location of the company influence the exposure levels. Conclusions: This study confirms the previous findings about occupational exposure to wood dust (mainly in wood industry and among woodworking machine operators) and suggests further investigations on other risk sectors (building and repairing of ships and boats). The potential of the occupational exposure database as a source of data for exposure assessment and surveillance is also confirmed.